How voles adapt to subterranean lifestyle: Insights from RNA-seq - Bondareva, Olga; Petrova, Tatyana; Bodrov, Semen; Gavrilo, Maria; Smorkatcheva, Antonina; Abramson, Natalia (Frontiers in Ecology and Evolution, 2023)
Life under the earth surface is highly challenging and associated with a number of morphological, physiological and behavioral modifications. Subterranean niche protects animals from predators, fluctuations in environmental parameters, but is characterized by high levels of carbon dioxide and low levels of oxygen and implies high energy requirements associated with burrowing. Moreover, it lacks most of the sensory inputs available above ground. The current study describes results from RNA-seq analysis of four subterranean voles from subfamily Arvicolinae: Prometheomys schaposchnikowi, Ellobius lutescens, Terricola subterraneus, and Lasiopodomys mandarinus. Original RNA-seq data were obtained for eight species, for nine species, SRA data were downloaded from the NCBI SRA database. Additionally assembled transcriptomes of Mynomes ochrogaster and Cricetulus griseus were included in the analysis. We searched for the selection signatures and parallel amino acid substitutions in a total of 19 species. Even within this limited data set, we found significant changes of dN/dS ratio by free-ratio model analysis for subterranean Arvicolinae. Parallel substitutions were detected in genes RAD23B and PYCR2. These genes are associated with DNA repair processes and response to oxidative stress. Similar substitutions were discovered in the RAD23 genes for highly specialized subterranean Heterocephalus glaber and Fukomys damarensis. The most pronounced signatures of adaptive evolution related to subterranean niche within species of Arvicolinae subfamily were detected for Ellobius lutescens. Our results suggest that genomic adaptations can occur very quickly so far as the amount of selection signatures was found to be compliant with the degree of specialization to the subterranean niche and independent from the evolutionary age of the taxon. We found that the number of genomic signatures of selection does not depend on the age of the taxon, but is positively correlated with the degree of specialization to the subterranean niche.